2021
DOI: 10.1016/j.midw.2021.103128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coronavirus disease 2019 in pregnancy and maternal and fetal outcomes: Retrospective analytical cohort study

Abstract: Objective Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has caused many deaths and complications worldwide. However, limited data are available about COVID-19 during pregnancy. This study aimed to assess the epidemiological and clinical features of COVID-19, and the adverse maternal and fetal outcomes. Design This retrospective analytical cohort study was conducted on all pregnant women with confirmed COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(75 reference statements)
0
11
1
1
Order By: Relevance
“…This is in accordance with other studies in the Middle East as well as in other worldwide countries such as the United States ( Hirshberg et al, 2020 ) and China ( Chen H et al, 2020 ). In Iranian pregnant women, the most common reported symptoms of COVID-19 were fever, cough, and dyspnea ( Kazemi Aski et al, 2020 , 2021 ; Motlagh et al, 2020 ; Pirjani et al, 2020 ; Sattari et al, 2020 ; Akbarian-Rad et al, 2021 ; Alipour et al, 2021 ; Samadi et al, 2021 ; Vaezi et al, 2021 ; Vizheh et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021b ). Lymphopenia and elevated C-reactive protein levels ( Pirjani et al, 2020 ; Akbarian-Rad et al, 2021 ; Vaezi et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021a , b ), in addition to Elevated lactate dehydrogenase (LDH; Kazemi Aski et al, 2020 ; Abedzadeh-Kalahroudi et al, 2021a ), were the most common laboratory findings observed.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
See 4 more Smart Citations
“…This is in accordance with other studies in the Middle East as well as in other worldwide countries such as the United States ( Hirshberg et al, 2020 ) and China ( Chen H et al, 2020 ). In Iranian pregnant women, the most common reported symptoms of COVID-19 were fever, cough, and dyspnea ( Kazemi Aski et al, 2020 , 2021 ; Motlagh et al, 2020 ; Pirjani et al, 2020 ; Sattari et al, 2020 ; Akbarian-Rad et al, 2021 ; Alipour et al, 2021 ; Samadi et al, 2021 ; Vaezi et al, 2021 ; Vizheh et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021b ). Lymphopenia and elevated C-reactive protein levels ( Pirjani et al, 2020 ; Akbarian-Rad et al, 2021 ; Vaezi et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021a , b ), in addition to Elevated lactate dehydrogenase (LDH; Kazemi Aski et al, 2020 ; Abedzadeh-Kalahroudi et al, 2021a ), were the most common laboratory findings observed.…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
“…This in accordance with other studies conducted in the United States and the United Kingdom where it was found that hospitalized women with COVID-19 and have comorbidities, are more prone to severe illness ( Knight et al, 2020 ; Zambrano et al, 2020 ). Although the majority of the pregnant women with COVID-19 were hospitalized, a minority of ICU admissions and maternal death were observed ( Pirjani et al, 2020 ; Sattari et al, 2020 ; Alipour et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021a ). The most common mode of delivery of infected pregnant women was a cesarean section, performed mostly under obstetric indication ( Pirjani et al, 2020 ; Alipour et al, 2021 ; Vaezi et al, 2021 ; Vizheh et al, 2021 ; Abedzadeh-Kalahroudi et al, 2021a ), rather than due to complications of COVID-19 ( Abedzadeh-Kalahroudi et al, 2021a ).…”
Section: Pregnant Women and Neonatesmentioning
confidence: 99%
See 3 more Smart Citations